The Efforts to Prevent and Overcome Criminal Acts of Money Politics - Bambang Tri Bawono; Andri Winjaya Laksana (LAW FACULTY UNISSULA, 2025)
One of the problems that often plagues the Indonesian nation is related to the crime of money politics. The crime of money politics is one of the ironies that has never been resolved to this day. In fact, the occurrence of these crimes is carried out simultaneously by the community. The type of research used in this study is sociological legal research using a qualitative approach. The results of the study state that the legal construction of the crime of money politics in the concept of legal certainty has been regulated in Government Regulation in Lieu of Law (Perpu) No. 1 of 2022 concerning Amendments to Law No. 7 of 2017 concerning General Elections and Law No. 6 of 2020 concerning Perpu No. 2 of 2020 concerning the Third Amendment to Law No. 1 of 2015 concerning the Stipulation of Perpu No. 1 of 2014 concerning the Election of Governors, Regents, and Mayors into Law. While efforts are being made to combat the occurrence of money politics, it is necessary to reconstruct that recipients should be allowed to receive money politics, but what is prohibited is only related to openly saying to choose a candidate for leader because it is contrary to the principle of secrecy.